The significance of Harlem Renaissance in American literature – “New Negro” - Ziyodakhon Gulomova (Zien Journals, 2021)
The article outlines the vital role of Harlem Renaissance in world literature, especially American literature and the appearance of the term New Negro during that period. It categorizes events into Old Negro and New Negro and compares similarities and differences between them. With this regard, it collects piece of writings of several scholars who saw Harlem Renaissance both as a literary and civil movement.
Keywords: Harlem Renaissance; movement; literary tendency; jazz age